The synthesis of wrightiadione via directed remote metalation - Nopporm Thasana (2018)
The application of directed remote metalation (DreM) and electrophilic substitution is reported for the synthesis of wrightiadione using N,N-diethylcarboxamide as a directed metalation group (DMG) and electrophilic group. The lithiation of N,N-diethylisoflavone-2′-carboxamide with LDA gave a carbanion at C-2 which further cyclized to wrightiadione.